2023
DOI: 10.1021/acs.biochem.2c00680
|View full text |Cite
|
Sign up to set email alerts
|

Putative Protein Interactome of the Rhomboid Protease RHBDL4

Abstract: The physiological functions of the rhomboid-related protein 4 (RHBDL4) are emerging, but their molecular details remain unclear. Because increased expression of RHBDL4 has been clinically linked to poorer outcomes in cancer patients, this association urgently demands a better understanding of RHBDL4. To elucidate the molecular interactions and pathways that RHBDL4 may be involved in, we conducted proximity-dependent biotin identification (BioID) assays. Our analyses corroborated several of the expected protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Likewise, RHBDL4 was suggested to organize GPCR-mediated trafficking events like for the signaling molecule TGFα (Wunderle et al , 2016). Using BioID proximity assays, it was indeed shown that RHBDL4 interacts with dozens of other proteins likely through interactions not related to proteolysis further supporting non-catalytic functions of RHBDL4 (Hsiao et al , 2023; Ikeda & Freeman, 2019). Remarkably, we found an increased catalytic activity of RHBDL4 at low cellular cholesterol levels (Paschkowsky et al , 2018), while β- and γ-secretases show an increased activity at high cellular cholesterol levels (Holmes et al , 2012; Kalvodova et al , 2005; Marquer et al , 2011; Osenkowski et al , 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Likewise, RHBDL4 was suggested to organize GPCR-mediated trafficking events like for the signaling molecule TGFα (Wunderle et al , 2016). Using BioID proximity assays, it was indeed shown that RHBDL4 interacts with dozens of other proteins likely through interactions not related to proteolysis further supporting non-catalytic functions of RHBDL4 (Hsiao et al , 2023; Ikeda & Freeman, 2019). Remarkably, we found an increased catalytic activity of RHBDL4 at low cellular cholesterol levels (Paschkowsky et al , 2018), while β- and γ-secretases show an increased activity at high cellular cholesterol levels (Holmes et al , 2012; Kalvodova et al , 2005; Marquer et al , 2011; Osenkowski et al , 2008).…”
Section: Discussionmentioning
confidence: 89%
“…A remarkable feature of APP is its processing by a myriad of proteases, besides α-, βand γ-secretases, multiple others such as MT5-MMP, RHBDL4, HtrA2, meprin-β, and possibly MT3-MMP. However, it remains elusive which pathways are active in which cell types at what stage and how they may be regulated (Ahmad et al, 2006;Bien et al, 2012;Huttunen et al, 2007;Park et al, 2006;Zhang et al, 2015). The relevance of Aη peptides in Alzheimer's disease is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, RHDBL4 could directly bind to ubiquitinated β-catenin via its UIM and target it for proteasomal degradation. As RHBDL4 is in part located in the peri-nuclear areas of the ER (Lastun et al, 2022) and our BioD data show that RHBDL4 interacts with nuclear pore complex components like nucleoporin NDC1 and integral proteins of the inner nuclear membrane such as MAN1 (Hsiao et al, 2023), it is possible that RHBDL4 encounters β-catenin while it translocates to the nucleus. Our BioID data also revealed α-catenin as a putative interactor of RHBDL4 (Hsiao et al, 2023).…”
Section: Discussionmentioning
confidence: 80%
“…As RHBDL4 is in part located in the peri-nuclear areas of the ER (Lastun et al, 2022) and our BioD data show that RHBDL4 interacts with nuclear pore complex components like nucleoporin NDC1 and integral proteins of the inner nuclear membrane such as MAN1 (Hsiao et al, 2023), it is possible that RHBDL4 encounters β-catenin while it translocates to the nucleus. Our BioID data also revealed α-catenin as a putative interactor of RHBDL4 (Hsiao et al, 2023). Interestingly, α-catenin is a known negative regulator of the Wnt/β-catenin signalling pathway via direct cytosolic sequestering of β-catenin or interaction with adenomatous polyposis coli (APC), a member of the destruction complex responsible for β-catenin degradation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation